2022
DOI: 10.1108/bfj-05-2021-0593
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the awareness of nutritional benefits of millets amongst women in Bangalore

Abstract: PurposeThe goal of the present study is to examine the degree of knowledge amongst Indian women about millet grain and its nutritional advantages. Millet is regarded to be five times more nutritious than rice and wheat. Despite the fact that millet contributes to 10% of India's food grain basket and has an annual production of 18 million tonnes, it is not consumed in the same proportion as mainstream cereals (that is rice and wheat). As a result, the study's primary objective is to determine the level of aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…PMO found a positive and significant effect on attitude, PBC and recycling behavioural intentions supporting the current contention and adding substantial evidence in the Indian youth context (Aboelmaged, 2021; Chen, 2020; Liu et al , 2020a, 2020b, 2020c; Wu et al , 2022). The results are evident that personal moral obligations are being formed/altered by the influence of social pressure from family and peer groups (subjective norms) (Rizwana et al , 2022; Liu et al , 2020a, 2020b, 2020c; Wu et al , 2022). These relationships have not been tested so far in environmental behaviour, specifically not among the Indian youth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PMO found a positive and significant effect on attitude, PBC and recycling behavioural intentions supporting the current contention and adding substantial evidence in the Indian youth context (Aboelmaged, 2021; Chen, 2020; Liu et al , 2020a, 2020b, 2020c; Wu et al , 2022). The results are evident that personal moral obligations are being formed/altered by the influence of social pressure from family and peer groups (subjective norms) (Rizwana et al , 2022; Liu et al , 2020a, 2020b, 2020c; Wu et al , 2022). These relationships have not been tested so far in environmental behaviour, specifically not among the Indian youth.…”
Section: Discussionmentioning
confidence: 99%
“…Further, empirical studies on pro-environmental behaviour determinants support the utility of adding PMO to the TPB model (Rizwana et al, 2022;Wu et al, 2022;Bamberg and Mo ¨ser, 2007). Taufique and Vaithianathan (2018) found that moral obligation has a better explanation power to predict behavioural intentions than attitude and subjective norms in the recycling behaviour domain.…”
Section: Identification Of Extended Theory Of Planned Behaviour Model...mentioning
confidence: 96%
See 3 more Smart Citations